Vibrational Analysis of Phenyl Butazone - Krishanakumar, V.; Sundareshan, N.; Natarajan, A. (Asian Journal of Chemistry, 2010)
The laser Raman spectrum of phenyl butazone was recorded in the region 4000–200 cm–1 and its fourier transform infrared spectrum in the region 4000–400 cm–1 . The spectra have been analysed assuming C1 point group symmetry. Probable assignments to the observed bands have been made with the help of magnitude and intensities of the recorded spectra.